Question #6225

x=y-8 and -x-y=0 you suppose to be solving system using substitution

Expert's answer

Substitute x which is given by the first equation( x=y-8) into the second equation:

-(y-8)-y=0

now open the braces . As long as "-" is before the braces we should change the sign of terms inside the braces when opening them:

-y+8-y=0

-2y+8=0

2y=8

y=4

now find x from the first equation by substituting y=4:

x=4-8=-4

Thus the answer is x=-4, y=4

-(y-8)-y=0

now open the braces . As long as "-" is before the braces we should change the sign of terms inside the braces when opening them:

-y+8-y=0

-2y+8=0

2y=8

y=4

now find x from the first equation by substituting y=4:

x=4-8=-4

Thus the answer is x=-4, y=4

## Comments

## Leave a comment